Effect of premedication with subcutaneous adrenaline on the pharmacokinetics and immunogenicity of equine whole IgG antivenom in a rabbit model - Herrera Vega, María (2017)
Subcutaneous administration of a low dose of adrenaline is used to prevent the early adverse reactions (EARs) induced by snake antivenoms. We used a rabbit model to study the effect of premedication with adrenaline on the potential of antivenoms to exert therapeutic effects and to induce late adverse reactions. We found that premedication with adrenaline did not change the heart rate or blood pressure of normal rabbits, but reduced the rise in temperature in rabbits previously sensitized with antivenom. Pharmacokinetic studies suggest that premedication with adrenaline does not affect the ability of the antivenom to exert the initial control of envenomation nor the susceptibility of rabbits to develop recurrence of antigenemia and envenomation. Our results also indicate that it is unlikely that premedication with adrenaline decreases the incidence of late reactions induced by the antivenom administration, although it reduces the extent of early reactions.